Two boxing is not the rational option - Noonan, Harold (Wiley, 2015)
In the standard Newcomb scenario two-boxing is not the rational act and, in general, in Newcomb-style cases the ‘two-boxing’ choice is not the rational act. Hence any decision theory which recommends two-boxing is unacceptable.